Breastfeeding rates in Israel and their health policy implications - Deena R. Zimmerman; Nati Brooks; Janice Wasser; Linoy Vaknin-Alon; Tunie Dweck; Sharon Alroy-Preis (Israel Journal of Health Policy Research)
Abstract Background Monitoring breastfeeding rates has important health policy implications, as breastfeeding has significant positive impacts on maternal and child health and healthcare costs. This up-to-date, national, population-based breastfeeding rates study in Israel provides important information for health policy development. Methods Breastfeeding rates were determined for the years 2016–2022 by retrospective analysis of Machshava Briah electronic medical records used by many Israeli Maternal and Child Health Clinics. This reflects approximately 70% of Israeli children with a nationwide distribution. Comparisons were conducted measuring breastfeeding rates over time and between different sub-groups. Results The dataset consists of 945,437 infant records. The percentages of women with any breastfeeding as well as exclusive breastfeeding have shown a gradual decline annually from 2016 to 2022 and are lower than international goals. Sub-group analyses were conducted for 2022. Breastfeeding rates were higher among multipara mothers (versus primapara). Singleton mothers had much higher breastfeeding rates than twin mothers with the difference even more pronounced in exclusive breastfeeding rates. Mothers of preterm infants (< 37 weeks) and low birthweight infants breastfed less than mothers of full term infants and normal birthweight and were less likely to exclusively breastfeed. Mothers living in urban areas had the highest rates of breastfeeding and those living in rural areas had the lowest. A subanalysis performed at two months postpartum for 2022 found the effect of maternal age with the highest rates of breastfeeding among 20–24 year old mothers. Inter-pregnancy interval also had an effect with the highest rates among those whose last pregnancy was 21–33 months ago and the lowest rates among those with an interval of < 1 year. Conclusions The population-based data provides an important baseline marker. This study shows a drop in breastfeeding rates, indicating a need to investigate reasons for discontinuing breastfeeding and identifying possible areas for offering support. This data and similar follow-up studies provide the background evidence to warrant that Ministry of Health policies in the hospitals and in the community, help accomplish their goals.